Neural mechanism of a sex-specific risk variant for posttraumatic stress disorder in the type I receptor of the pituitary adenylate cyclase activating polypeptide - Pohlack, Sebastian; Ruttorf, Michaela; Schad, Lothar R.; Rietschel, Marcella; Flor, Herta (Biological psychiatry)
Posttraumatic stress disorder (PTSD) is a frequent anxiety disorder with higher prevalence rates in female patients than in male patients (2.5:1). Association with a single nucleotide polymorphism (rs2267735) in the gene ADCYAP1R1 encoding the type I receptor (PAC1-R) of the pituitary adenylate cyclase activating polypeptide has been reported with PTSD in female patients. We sought to identify the neural correlates of the described PAC1-R effects on associative learning. In a reverse genetic approach, we examined two independent healthy samples (N1 = 112, N2 = 73) using functional magnetic resonance imaging during cued and contextual fear conditioning. Skin conductance responses and verbal self-reports of arousal, valence, and contingency were recorded. We found that PAC1-R modulates the blood oxygenation level-dependent response of the hippocampus. Specifically, we observed decreased hippocampal activity during contextual, but not during cued, fear conditioning in female participants carrying the PAC1-R risk allele. We observed no significant differences in conditionability for skin conductance responses, verbal reports, or activation in other brain regions between the genotype groups in female participants. Our results suggest that impaired contextual conditioning in the hippocampal formation may mediate the association between PAC1-R and PTSD symptoms. Our findings potentially identify a missing link between the involvement of PAC1-R in PTSD and the well-established structural and functional hippocampal deficits in these patients.
Gesehen am 25.10.2017